Usulan Perbaikan Sistem Kanban untuk Optimalisasi Pada PT Torishima Guna Indonesia - Ira Puspita; Ririn Regiana Dwi Satya (Universitas Indraprasta PGRI Jakarta, 2020)
PT Torishima Guna Indonesia is a manufacturing company that produces water pumps. In a production system that is run using a hybrid, which is where you can make to stock and make to order, but in one product that uses the make to order system, the ETA-N product. ETA-N products are very popular products, but PT Torishima Guna Indonesia often does not meet demand, due to problems on the production floor. PT Torishima Guna Indonesia often accumulates WIP (work in process) in the warehouse, because the spare parts needed are not sent by the supplier or are late in sending spare parts, resulting in increased storage costs. From the problems that have occurred, what is done by implementing kanban is expected to suppress the weaknesses that occur in the production system in the company. Kanban is a pull system approach that relies on authorization to control the amount of production to be carried out by the company, in order to control the raw materials of a product based on forecasting consumer demand. The purpose of this study is to determine the implementation of the kanban system at PT Torishima Guna Indonesia, to determine the factor of late delivery of components for PT Torishima Guna Indonesia, to design a system for providing material supply in the production process so as to reduce inventory, Work in Process (WIP) at each production process. In implementing this proposal, it is evident that the reduction in inventory costs is clearly visible, namely by 45% in 2017 and 72% in 2018.